Relationship of age at puberty and postpartum interval to estrus in Angus x Hereford and Brahman x Hereford Females - Patterson, D.J.; Corah, L.R.; Brethour, J.R.; Negus, W.R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Records of age at puberty (AAP) and postpartum interval to estrus (PPI) for heifers calving first at 2 years of age were used to determine the relationship between the two reproductive parameters. In Brahman x Hereford (BxH) females, there was no relationship between AAP and PPJ. In Angus x Hereford (AxH) females, PPI increased as AAP decreased. The data suggest that heifers heavier at weaning reach puberty younger, but PPJ may be longer following their first calving. Heifers larger at weaning may need to be managed differently to improve performance during the first postpartum period.
Keywords: Beef; Age; Puberty; Estrus